Faktor-faktor yang Mempengaruhi Volume Ekspor Kopi dari Kabupaten Aceh Tengah ke Amerika Serikat - Afriamah Afriamah; Zulkarnain Lubis; Mitra Musika Lubis (Jurnal Agriuma, 2021)
Indonesia is one of the world's largest coffee producers, it can be seen from the amount of exports from Indonesia for coffee export. In the past few years, several companies have carried out massive expansion to get Gayo coffee from Central Aceh Regency and Bener Meriah. The purpose of this study was to analysis what factors influence the volume of Gayo coffee exports from Central Aceh Regency to the United States. The data collection method using the documentary method is the data obtained and viewed by the document in accordance with the variables in the research model in the period 2013-2017. Data collected is secondary data. The analytical method used is multiple linear regression with the method used is the Ordinary Least Square (OLS) Method. From the research using multiple linear regression analysis obtained that variables which have significant effect to the export demand of Gayo Coffee from the United States is Global Coffee Prices. While the production of domestic Gayo coffee, the exchange rate of dollars against the rupiah and the price of foreign Gayo coffee are not significant to the demand for export of Gayo coffee to the United States.